STRATEGI PROMOSI “LANGKAH HALAL WEDDING ORGANIZER” DALAM MENCAPAI TARGET PASAR: STUDI PERSONALITAS DAN MOTIVASI YANG MENDASARI KONSUMEN DALAM MEMPERCAYAI “LANGKAH HALAL WEDDING ORGANIZER” - Nona Ratna Wulaksi, Achiriah, Abdul Rasyid (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2022)
Abstract: The study is a qualitative type of descriptive study, the data in the study is derived from primary and secondary data. The data-collecting technique used consists of interviews, direct observations, and documenting the results of this study explaining that either way or promotional strategies are done by the